Altitude variations in the thermosphere mass density response to geomagnetic activity during the recent solar minimum. Issue 3 (7th March 2014) - Liu, X.; Thayer, J. P.; Burns, A.; Wang, W.; Sutton, E.
Abstract Accelerometer data from coplanar orbits of Challenging Minisatellite Payload (CHAMP) and Gravity Recovery and Climate Experiment (GRACE) satellites were used to study the complex altitude and latitude variations of the thermosphere mass density response to geomagnetic activity during 1–10 December 2008 near 09 LT. Helium number densities near 500 km altitude were extracted from the CHAMP and GRACE measurements and clearly show the presence of a winter hemisphere helium bulge. This recent extreme solar minimum indicates that wintertime helium concentrations exceed NRLMSISE‐00 model estimates by 30%–70% during quiet geomagnetic activity after adjusting F10.7 input into MSIS. The perturbation in mass density from quiet to active conditions is found to be less enhanced in the winter hemisphere at the higher GRACE altitudes (25%) than at the lower CHAMP altitudes (60%) and is attributed to dynamic behavior in the helium/oxygen transition. The investigation revealed the maximum storm time density perturbation to occur near the He/O transition region with a much weaker maximum near the O/N2 transition region. The altitude of maximum density perturbation occurs where the perturbation in the weighted pressure scale height is equal and opposite to the perturbation in the weighted mean molecular weight scale height. The altitude structure of density scale height perturbation is significantly influenced by the changes in the molecular weight scale height and can account for 50% of the change in mass density scale height in a region correspondingly close to the He/O transition during the 2008 solar minimum period.